装置、系统、方法以及记录介质 (2025)
本申请涉及一种装置、系统、方法以及记录介质。提供了一种装置，包括：取得部，从能够控制朝向的相机取得摄像图像；显示控制部，使摄像图像显示在显示画面上；检测部，在显示画面内检测用户正在观看的被摄体；以及朝向变更部，变更相机的朝向，以使被摄体不脱离相机的摄像区域。 [Solving Means] An apparatus comprising an acquisition unit configured to acquire a captured image from a camera that is capable of controlling an orientation, a display control unit configured to display the captured image onto a display screen, a detection unit configured to detect, within the display screen, a subject at which a user is looking, and an orientation changing unit configured to change an orientation of the camera in such a way that the subject does not fall out of an imaging region of the camera is provided.